The naval miscellany. - Vale, Brian (Publications of the Navy Records Society, 2017)
Brian Vale is a naval historian with degrees from Keele and King's College London. A life-long member of the Society for Nautical Research and the Navy Records Society, he has long specialised in Anglo-South American maritime history.